Does Embryonic Culture Environment Affect Ploidy Rates in ART Cycles: A Single Center Study in UK - R Odia; VG Xavier; C Heath; W Saab; O Ozturk; S Seshadri; P Serha (JRI, 2022)
Background: The purpose of the current study was to assess whether embryonic culture conditions has an impact on embryo ploidy in a preimplantation genetic testing for aneuploidy (PGT-A) cycle. Methods: In this retrospective single center cohort study, a total of 1099 blastocysts from 278 PGT-A cycles were analyzed. The generated blastocysts were biopsied on days 5 and 6. Inseminated oocytes were allocated in different incubators (benchtop and time lapse) and assisted zona hatching was performed on day 3 of embryo development to facilitate the biopsy process which was performed on days 5 and 6 (blastocyst stage). Results: The average age across the groups was 38.7±3.6 years and the total number of mature eggs was 2912 which were randomly distributed across both incubators. The euploidy rate obtained from both groups showed a higher proportion of euploid embryos in the TLM incubator (37.03%, 95% CI 31.9-42.1) compared to those cultured in the BT incubator (30.4%, 95% CI 23.1-37.7). Regression analysis showed that female age remains to be the key variable driving euploidy rates (0.85, 95% CI 0.82-0.88) although incubator type could be an important covariable (0.54, 95% CI 0.45-0.59). A subgroup analysis of 74 single euploid embryo transfers showed comparable pregnancy and live birth rates. Conclusion: This large cohort study demonstrates that uninterrupted controlled culture environment provides increased probability to develop euploid embryo in a PGT-A cycle. However, further evaluation is required to assess how environmental culture conditions at a cellular level could affect epigenetic mechanisms in embryo development and higher aneuploidy rate.